Art therapy as counseling modality to help delinquent students - Wan Muhammad Baihaqi Wan Hamat; Abu Yazid Abu Bakar (Journal of Counseling, Education and Society, 2020)
The purpose of this psycho-educational group counseling is to provide knowledge and information to target groups on their delinquent problems. Delinquent is an attitude that violates the law  that society does not accept but not serious. Delinquent problems are often associated with adolescents either in primary school or high school. The participants were 26 students from one of the private schools in Selangor which are from form two and three. The process of selecting participants is through discussions with the school counselor, and the participants are those who have identified disciplinary records involved in delinquency issues. The researchers conducted four group counseling sessions. Participants were divided into three groups according to their disciplinary problems. The module used in this program is art therapy through “LEPAS” approach or known as Luah Emosi Positifkan Akal Sihat. The participants aware of their emotions and realize that what are they doing (disciplinary issues) is wrong and should be stopped as the results of the involvements in this psycho-educational program. The implications of this program are directed to the counseling practitioners whose can use the art approach in dealing with school discipline cases.